Sustainability content knowledge for teachers in accounting and controlling: a systematic literature review on industry approaches, practices and desired competences - Pargmann, Julia; Berding, Florian (Frontiers in Education, 2025)
IntroductionSustainable transformation is critical in the face of today’s challenges, with business at the center of sustainable development. Students in vocational business education need to integrate sustainability into decision-making processes, which are often based on accounting and controlling. These form a significant operational foundation, which is why sustainability should play an essential role here. Teachers need appropriate content knowledge and knowledge of industry needs.MethodsThis study uses a PRISMA-led systematic review and qualitative content analysis to explore the current discourse. The aim is to derive starting points for adequate content knowledge. 79 full texts were analyzed that link sustainability to accounting and/or controlling.ResultsThe literature shows a shift towards a comprehensive approach where sustainability permeates legal and profit-orientated operational aspects. Challenges exist in the integration of non-monetary information, with proposed solutions such as social and environmental accounting. Essential competences include sustainability awareness and ethical principles.DiscussionThe study emphasizes the need to integrate sustainability into education and recommends a process-oriented perspective to promote a multidimensional understanding.